2006
DOI: 10.1103/physrevlett.96.197208
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Magneto-Optics of Ferromagnetic Transition-Metal-Doped ZnO Thin Films

Abstract: Magneto-optic studies of ZnO doped with transition metals Co, Mn, V and Ti indicate a significant magnetic circular dichroism (MCD) at the ZnO band edge at room temperature, together with an associated dispersive Faraday rotation. Similar spectra occur for each dopant which implies that the ferromagnetism is an intrinsic property of the bulk ZnO lattice. At 10 K additional paramagnetic contributions to the MCD are observed, but above about 150K, the magnitude of the MCD signal is dominated by the ferromagnetis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
96
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(99 citation statements)
references
References 18 publications
3
96
0
Order By: Relevance
“…Reproducibly, exposure of Zn 1−x Co x O thin film to Zn vapor creates interstitial Zn defects and induces room-temperature ferromagnetism, and annealing the thin film in air quenches the ferromagnetism due to elimination of the interstitial Zn by oxidation. Neal et al 13 observed magnetic circular dichroism ͑MCD͒ signals with open hysteresis loop at the ZnO band edge of Co-doped ZnO thin films at room temperature, implying a splitting of the conduction band of ZnO through interaction with the magnetic moments of the Co ions. These observations rule out Co-cluster segregations or secondary phase formation as the origin of the ferromagnetism.…”
Section: Introductionmentioning
confidence: 99%
“…Reproducibly, exposure of Zn 1−x Co x O thin film to Zn vapor creates interstitial Zn defects and induces room-temperature ferromagnetism, and annealing the thin film in air quenches the ferromagnetism due to elimination of the interstitial Zn by oxidation. Neal et al 13 observed magnetic circular dichroism ͑MCD͒ signals with open hysteresis loop at the ZnO band edge of Co-doped ZnO thin films at room temperature, implying a splitting of the conduction band of ZnO through interaction with the magnetic moments of the Co ions. These observations rule out Co-cluster segregations or secondary phase formation as the origin of the ferromagnetism.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical predictions based on the local spin density approximation (LSDA), triggered extensive studies of ZnO:TM alloys with a special focus on ZnO:Co as the most promising candidate for a room-temperature ferromagnetic (FM) semiconductor [3]. Many experiments have been reported on this material fabricated by a variety of methods [4][5][6]; however, the magnetic properties of ZnO:Co still remain a controversial issue since the observed magnetic behavior appears to be strongly dependent on the preparation methods and is poorly reproducible. Ferromagnetism was reported for thin films and bulk samples of ZnO:Co with a very large spread of spontaneous magnetic moment from 6.1 m B /Co to 0.01 m B /Co accompanied by a Curie temperature well above room temperature [4][5][6][7][8][9].…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] For practical spintronic applications DMS with Curie temperature, Tc, above RT are required. Many promising oxides like TiO 2 , ZnO and SnO 2 and III-V semiconductor GaN doped with transition metal ions have been reported to exhibit ferromagnetic behavior near or above room temperature, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] but the origin of ferromagnetism in these systems is poorly understood. Oxide systems based on host semiconductor with high solubility of magnetic ions are highly desirable to form thermodynamically stable magnetic semiconductors.…”
mentioning
confidence: 99%